Fabrication of Photothermo-Responsive Drug-Loaded Nanogel for Synergetic Cancer Therapy - Ray Chang (Polymers, 2018)
Temperature stimulus, easy modulation in comparison to other environmental stimuli, makes thermo-responsive nanocarriers popular in the applications of controlled drug release for cancer therapy. In this study, photosensitive sodium copper chlorophyllin (SCC) was incorporated into thermo-responsive polymeric nanogels consisted of N-isopropylacrylamide and N-(hydroxymethyl)acrylamide. Significant heat was generated from the SCC-containing nanogels under the exposure to 532-nm green laser, and resulted in cell mortality. The thermo-responsive nanogel loaded with 5-FU, an anti-cancer drug, released the drug explosively when exposed to green laser. The combination of hyperthermia and temperature-induced drug release via green laser irradiation greatly enhanced cell mortality to a maximal extent. Such photothermo-responsive nanogel possesses a great potential in anti-cancer treatment.